Gold(III)-catalyzed chemoselective annulations of anthranils with N-allylynamides for the synthesis of 3-azabicyclo[3.1.0]hexan-2-imines - Song, Lina; Tian, Xianhai; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemical communications, 2019)
We herein report the gold(III)-catalyzed selective annulation of anthranils with N-allylynamides under mild conditions. By trapping the in situ-generated α-imino gold carbenes, 3-azabicyclo[3.1.0]hexan-2-imines were obtained in high synthetic efficiency. The reaction, which can be conducted in the gram scale, tolerates electron-rich and electron-deficient anthranils as well as a diverse set of functionalized ynamides (aryl- and alkyl-substituted terminal).